Juridical Analysis of the Rights and Position of Heirs in Inheritance Disputes: Case Study of Decision Number 9/Pdt.G/2024/PN Tbt - Ketaren, Marianne; Nasution, Abdul Haris; Nasution, Hani Riadho (PT. Anagata Sembagi Education, 2024)
This study delves into the rights and positions of heirs in inheritance disputes, with a detailed analysis of Decision No. 9/Pdt.G/2024/PN Tbt. The primary focus is on how Indonesian law recognizes and upholds the rights of heirs in conflicts over inheritance. The case in question involves the heirs of the late PO Siregar and Turena Br Hutauruk, who were in a legal battle over the division of land and buildings left by the deceased. The study explores the legal principles, evidence, and court decisions that determined the distribution of assets among the heirs. It examines how the court interpreted relevant inheritance laws and applied them to establish the rightful claims of each party involved. By scrutinizing the legal proceedings and outcomes, this research provides insights into the functioning of Indonesian inheritance law, particularly in adjudicating disputes among heirs. The findings contribute to a broader understanding of how inheritance rights are protected and enforced in the legal system